2005
DOI: 10.1007/s10720-005-0114-9
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Behavior of Alkali Zinc Phosphates

Abstract: Alkali zinc phosphates O 7 ) 5 , which can be prepared both by the solid-phase synthesis and through crystallization from a glass, are studied using high-temperature X-ray powder diffraction. The unit cell parameters as functions of the temperature in the range 20-700°C are analyzed, and the linear anisotropic thermal expansion coefficients are determined. The majority of these compounds are characterized by strong anisotropy of thermal expansion. It is found that the LiKZnP 2 O 7 compound exists in two polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Glass formation in the system ZnO-P 2 O 5 -SO 3 -Na 2 O was studied starting from the eutectic pyrophosphate 42Zn 2 P 2 O 7 -58Na 2 ZnP 2 O 7 [33,34] and varying the ratio of SO 3 /P 2 O 5 as well as the content of network modifiers (Table 1). In a first consideration, the focus was set on the ternary of ZnSO 4 -Zn 2 P 2 O 7 -Na 2 ZnP 2 O 7 , but it was found that the glass forming region extends to far beyond the ZnSO 4 -Na 2 ZnP 2 O 7 join (nominally adding an excess of sodium phosphate and/or sodium sulfate).…”
Section: Methodsmentioning
confidence: 99%
“…Glass formation in the system ZnO-P 2 O 5 -SO 3 -Na 2 O was studied starting from the eutectic pyrophosphate 42Zn 2 P 2 O 7 -58Na 2 ZnP 2 O 7 [33,34] and varying the ratio of SO 3 /P 2 O 5 as well as the content of network modifiers (Table 1). In a first consideration, the focus was set on the ternary of ZnSO 4 -Zn 2 P 2 O 7 -Na 2 ZnP 2 O 7 , but it was found that the glass forming region extends to far beyond the ZnSO 4 -Na 2 ZnP 2 O 7 join (nominally adding an excess of sodium phosphate and/or sodium sulfate).…”
Section: Methodsmentioning
confidence: 99%